기록관리 전문요원의 직무스트레스가 직무만족에 미치는 영향 - 심한울(Hanul Sim); 장우권(Wookwon Chang) (Journal of Records Management & Archives Society of Korea, 2021)
The purpose of this study is to find out how job stress and job satisfaction differ depending on the demographic characteristics of records management specialists in public institutions and how their job stress affects job satisfaction. A survey that employs the use of questionnaires gathering data about participants' jobs, job stress, and job satisfaction was given to 159 participants. Independent sample T test, Analysis of Variance (ANOVA) analysis, and correlation analysis were employed in analyzing the data through the survey. The following results were obtained. First, the average of the total job stress of professional personnel was 2.60. Second, there were differences between the job stress and job satisfaction of professional personnel depending on their age, employment type, education, salary, working institution, and service period. Third, the effect of job stress of professional personnel on job satisfaction is significant with all factors, excluding job demand and job satisfaction, boss conflict and job instability, peer conflict and job instability, job insecurity and inadequate compensation, and job instability and job satisfaction. Fourth and last, there is a higher job satisfaction when there is a higher job demand factor, which is the job stress of professional personnel. However, except for those with significant results, the higher the factors of peer conflict and inadequate compensation of job stress, the lower the job satisfaction except for showed significant results. 이 연구는 공공기관의 기록물관리 전문요원이 인구통계학적 특성에 따라 직무스트레스와 직무만족도가 어떤 차이가 있는지, 이들의 직무스트레스가 직무만족에 어떠한 영향을 미치는지를 파악하는데 있다. 이를 위해 직무와 직무스트레스, 직무만족을 반영한 설문조사(159부)를 하였다. 설문분석은 독립표본 T 검정, ANOVA 분석, 상관분석 등으로 이루어졌다. 그 결과, 1) 전문요원의 직무스트레스 총 평균은 2.60으로 나타났다. 2) 전문요원의 직무스트레스와 직무만족은 연령별, 고용형태, 학력, 급여, 근무기관, 근속기간에 따라 직무스트레스의 차이가 나타났다. 3) 전문요원의 직무스트레스가 직무만족에 미치는 영향에 대해서는 직무요구와 직무만족, 상사갈등과 직무불안정, 동료갈등과 직무불안정, 직무불안정과 보상부적절, 직무불안정과 직무만족 등을 제외한 나머지 요인에서 유의미한 결과를 보였다. 4) 전문요원의 직무스트레스인 직무요구 요인이 높을수록 직무만족은 같이 올랐다. 그러나 직무스트레스의 동료갈등요인과 보상부적절 요인이 높으면 높을수록 직무만족은 낮아졌다.